2004
DOI: 10.1155/2004/461392
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics at Initial Presentation and Impact of Dual Therapy on the Outcome of Bacteremic Streptococcus pneumoniae Pneumonia in Adults

Abstract: BACKGROUND:Approximately 10% of patients hospitalized with community-acquired pneumonia (CAP) are bacteremic. BacteremicStreptococcus pneumoniaepneumonia (BSPP) is the number one cause of mortality, representing up to 70% of all CAP deaths. In fact, all CAP guidelines have identified this issue as one of the most important issues when establishing their recommendations.OBJECTIVE:To assess the impact of dual antibiotic therapy in patients with BSPP.PATIENTS AND METHODS:All cases of BSPP in patients 18 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 28 publications
1
51
1
Order By: Relevance
“…WATERER et al [23] suggested that monotherapy may be suboptimal for patients with bacteraemic S. pneumoniae pneumonia, whatever treatment is given. Further studies [24][25][26][27] agree with these findings, but the controversy should be resolved by conducting a randomised clinical trial.…”
Section: Previous Studies In Copd Patients Have Suggested Thatmentioning
confidence: 79%
“…WATERER et al [23] suggested that monotherapy may be suboptimal for patients with bacteraemic S. pneumoniae pneumonia, whatever treatment is given. Further studies [24][25][26][27] agree with these findings, but the controversy should be resolved by conducting a randomised clinical trial.…”
Section: Previous Studies In Copd Patients Have Suggested Thatmentioning
confidence: 79%
“…In addition, rational antibiotic combination therapies associated with reduced mortality and were reported to produce better clinical outcome in patient who are at risk for treatment failure [8].…”
Section: Introductionmentioning
confidence: 99%
“…In several retrospective or nonrandomized prospective clinical studies, a survival benefit has been shown in patients with pneumococcal CAP treated with a combination of b-lactam antibiotics and macrolides compared with those treated with b-lactam monotherapy [61][62][63][64][65]. However, two large prospective cohort studies showed no difference between these two regimens [66,67].…”
Section: Macrolide Antibioticsmentioning
confidence: 99%